Bilateral strategic groups: The market for nontactical navy information systems - Galbraith, Craig S.; Merrill, Gregory B.; Morgan, George Parker (Strategic Management Journal, 1994)
Abstract Although recent studies of strategic groups have provided much insight into the nature of intra‐industry rivalry, most studies have focused on the strategies of seller firms. In this paper we argue that the bilateral exchange between groups of buyers and sellers in adjacent markets should be made explicit. Within this bilateral context, the market for non‐tactical Navy infomation systems is empirically examined. Strategic groups are developed for both seller and buyer industries, and the interaction between these groups are explored over time. In particular, two market interventions, the imposition of industrial funding procedures in 1984 and a Life‐Cycle requirement order in 1988, were examined with respect to their impact on seller/customer exchanges and vertical integration strategies. Significant changes in strategies were noted, and explained within a transaction cost framework.